2019
DOI: 10.1161/jaha.118.011013
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude of the Difference Between Clinic and Ambulatory Blood Pressures and Risk of Adverse Outcomes in Patients With Chronic Kidney Disease

Abstract: Background Obtaining 24‐hour ambulatory blood pressure ( BP ) is recommended for the detection of masked or white‐coat hypertension. Our objective was to determine whether the magnitude of the difference between ambulatory and clinic BP s has prognostic implications. Methods and Results We included 610 participants of the AASK (African American Study of Kidney Disease and Hypertension) Cohort Study who had clinic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 46 publications
1
10
1
6
Order By: Relevance
“…6 In patients with CKD, studies have shown conflicting results: some studies show no association of white-coat effect and cardiovascular disease, 10 whereas others show that patients with a white-coat effect are at higher risk for mortality. 13 In our cohort of patients who were mostly treated for hypertension, the presence of white-coat effect was not associated with a higher risk for cardiovascular outcomes, kidney outcomes, and mortality compared with participants with controlled BP. However, white-coat hypertension when defined using the lower threshold of 130/80 mm Hg was associated with higher risk of mortality, and white-coat hypertension was associated with higher risk of the kidney outcome in participants with lower levels of GFR.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…6 In patients with CKD, studies have shown conflicting results: some studies show no association of white-coat effect and cardiovascular disease, 10 whereas others show that patients with a white-coat effect are at higher risk for mortality. 13 In our cohort of patients who were mostly treated for hypertension, the presence of white-coat effect was not associated with a higher risk for cardiovascular outcomes, kidney outcomes, and mortality compared with participants with controlled BP. However, white-coat hypertension when defined using the lower threshold of 130/80 mm Hg was associated with higher risk of mortality, and white-coat hypertension was associated with higher risk of the kidney outcome in participants with lower levels of GFR.…”
Section: Discussionmentioning
confidence: 58%
“…[10][11][12] However, studies evaluating the association between masked uncontrolled hypertension and progression of kidney disease have demonstrated conflicting results; some, 10,11 but not all, studies have shown a higher risk of progression of kidney disease in patients with masked uncontrolled hypertension. 13,14 In a large and diverse cohort of participants with CKD, we demonstrate that the presence of masked uncontrolled hypertension is associated with high risk of cardiovascular disease and progression of kidney disease. This risk is independent of other risk factors that may influence these outcomes, including office BP, and consistent across subgroups of age, sex, race, and diabetes.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…To allow for flexibility in modeling the association between DCA and outcomes, we applied Cox proportional hazards models using penalized cubic splines with one knot. 24 We determined the optimal number of degrees of freedom (df) and placement of the knot in cubic splines by comparing models with different dfs and choosing the model with minimum AIC or BIC. 25,26 The knot was located at the median of DCA value 68.45 ng/ml, and was defined as the reference value (hazard ratio [HR] =1.0).…”
Section: Discussionmentioning
confidence: 99%
“… 12 Ku et al showed the clinical relevance of these conditions among 610 participants in the AASK trial, which revealed a U-shaped association between clinic and ambulatory SBP difference and an increased mortality but no ESKD risk. 26 However, the generalizability of this trial to all hypertensive CKD patients is unknown. The ongoing 4-year prospective randomized MASked-unconTrolled hypERtension management based on office BP or on ambulatory blood pressure measurement (MASTER) study may help clarify this ambiguity if it indicates that ABPM-based treatment strategies slow target organ damage and reduce future CV events.…”
Section: Goals Of Bp Reduction and Consensus Targetsmentioning
confidence: 99%